Arranjo de plantas, características agronômicas e produtividade de soja - Costa, Élide Dalzoto [UNESP] (2013)
The raise in the grain yield of soy bean cultivation has constituted a great challenge, and among the new management practices in study to maximize the productive potential is the use of different spatial plants arrangements. The work had as a objective to evaluate effects of the soy bean plants arrangement of indeterminate growth type on product ion components and grain productivity. The experiment was lead at the ABC Foundation experimental station, in the city of Arapoti, PR, during the agricultural year of 2010/2011. The experimental lineation used was the one with randomized blocks in split po rtions and four repetitions, with the main portion consisted of three spacings between rows (20, 40 and 60 cm) and the subportions by the combination of four plant populations (150, 250, 350 and 450.000 plants ha - 1 ) and two cultivars (BMX PotênciaRR and NA 5909RG). The evaluated characteristics were the leaf closure of plants between sowing rows, the leaf area index, the plant height average, the insertion average height of the first pod, the average number of branches per plant, the average number of pods p er plant, the average number of grains per plant, the average number of grains per pod, the mass of 100 grains and the grains productivity. According to the obtained results, it was concluded that changes in the spatial arrangement of soy bean plants of ind eterminate growth type can positively influence on grains productivity and its components. It was found increased grain productivity with the reducing of spacing between lines, regardless of plants population and cultivar. The raise of soy bean plants popul ation in the sowing row caused reductions in the number of pods per plant, grains per plant and the number of branches; on the other hand, it increased the mass of 100 grains, the plant height average and the insertion average height of the first pod